Differential seedling responses of chickpea varieties to hexavalent chromium (VI) stress under controlled conditions - Muhammad Hammad; Afifa Kainat Rani; Laraib Chouhdary; Muhammad Kabir; Patricio R. De los Ríos-Escalante; Muhammad Aslam (PLoS ONE, 2026)
Hexavalent chromium (Cr VI) contamination infiltration in soil due to industrial activities has become a sever threat to Pakistan’s agricultural productivity. Recent surveys report soil chromium concentrations in agricultural–industrial interfaces of Punjab and Khyber Pakhtunkhwa reaching 100 mg/kg, exceeding the WHO permissible limit (1.5 mg/kg) by more than 50-fold. Chickpea, a widely cultivated crop in Pakistan also faces productivity threats from Cr (VI). This study evaluates the differential seedling responses of two Pakistani chickpea varieties (CM-72 and CM-98) to hexavalent chromium stress (0µM to 100µM) under controlled conditions to address a critical research gap. A fully randomized experimental design (CRD) with five replicates per treatment was utilized, assessing germination metrics, root and shoot lengths, root collar diameter, and biomass over a period of 14 days. Statistical evaluations (ANOVA, Pearson correlation, PCA) indicated substantial varietal differences. Both varieties showed significant (p < 0.05) dose-dependent reductions in germination rates, growth, and biomass; however, CM-72 exhibited greater tolerance. At a concentration of 100 µM Cr VI, CM-72 achieved 90% germination (compared to 80% in CM-98), with moderate declines in root length (39% compared to 77% in CM-98), shoot length (76% compared to 90%), and biomass (34% dry weight loss in comparison to 59% in CM-98). Multivariate analysis revealed strong associations between growth inhibition and chromium stress, with PCA differentiating between structural (root collar diameter) and temporal (germination delay) effects. These results highlight the resilience of CM-72, likely attributable to metabolic and antioxidative adaptations, making it a potential candidate for cultivation in areas contaminated with chromium. The relative tolerance of CM-72 may relate to underlying physiological or biochemical traits that warrant investigation in future studies. This research offers essential insights into the responses of chickpea varieties to Cr VI stress, highlighting the necessity for biochemical and molecular studies to clarify tolerance mechanisms and support sustainable agricultural practices in regions impacted by heavy metals.